Calcium/Calmodulin-Mediated Defense Signaling: What Is Looming on the Horizon for AtSR1/CAMTA3-Mediated Signaling in Plant Immunity - Yuan, Peiguo; Tanaka, Kiwamu; Poovaiah, B. W. (Frontiers in Plant Science, 2022)
Calcium (Ca2+) signaling in plant cells is an essential and early event during plant-microbe interactions. The recognition of microbe-derived molecules activates Ca2+ channels or Ca2+ pumps that trigger a transient increase in Ca2+ in the cytoplasm. The Ca2+ binding proteins (such as CBL, CPK, CaM, and CML), known as Ca2+ sensors, relay the Ca2+ signal into down-stream signaling events, e.g., activating transcription factors in the nucleus. For example, CaM and CML decode the Ca2+ signals to the CaM/CML-binding protein, especially CaM-binding transcription factors (AtSRs/CAMTAs), to induce the expressions of immune-related genes. In this review, we discuss the recent breakthroughs in down-stream Ca2+ signaling as a dynamic process, subjected to continuous variation and gradual change. AtSR1/CAMTA3 is a CaM-mediated transcription factor that represses plant immunity in resting plants. Stress-triggered Ca2+ spikes impact the Ca2+-CaM-AtSR1 complex to control plant immune response. We also discuss other regulatory mechanisms in which Ca2+ signaling activates CPKs and MAPKs cascades followed by regulating the function of AtSR1 by changing its stability, phosphorylation status, and subcellular localization during plant defense.